Effect of reinforced fibers on the vibration characteristics of fibers reinforced composite shaft tubes with metal flanges. (1st November 2021) - Qi, Liangliang; Li, Caihong; Yu, Xuduo; Min, Wei; Shi, Han; Tao, Lei; Wang, Hao; Yu, Muhuo; Ni, Lei; Sun, Zeyu
Abstract: The fiber-reinforced composite (FRP) shaft need to consider vibration performance of the transmission system to improve work efficiency, comfort, service life and safety. The fiber materials and tubes containing metal connectors are important parts of the FRP shaft so that the study on the vibration performance of these two key components is of great significance for an in-depth understanding of the vibration performance of shafts. The finite element analysis (FEA), pulse vibration excitation technique (PVET) and formula computing were used to study the effect of the vibration characteristics of shafts. This study revealed that increasing the modulus of the fiber is one of the effective methods to increase the natural frequency of the FRP tube and the damping ratio of the carbon FRP tubes were slightly smaller compared with basalt and glass fiber. The FEA of FRP tube results were not distinct from the measured and calculated results so that these FEA results were relatively reliable. The damping of the tube with metal flanges at both ends were weaken compared the FRP tube. This work will be of great significance to the optimization design of the vibration performance of FRP shafts.